Neurovision: Neural bases of binocular vision and coordination and their implications in visual training programs - Olivier A. Coubard (Frontiers Research Topics, 2015)
Binocular vision is achieved by five neurovisual systems originating in the retina but varying in their destination within the brain. Two systems have been widely studied: the retino-tectal or retino-collicular route, which subserves an expedient and raw estimate of the visual scene through the magnocellular pathway, and the retino-occipital or retino-cortical route, which allows slower but refined analysis of the visual scene through the parvocellular pathway. But there also exist further neurovisual systems: the retino-hypothalamic, retino-pretectal, and accessory optic systems, which play a crucial role in vision though they are less understood. The retino-pretectal pathway projecting onto the pretectum is critical for the pupillary or photomotor reflex. The retino-hypothalamic pathway projecting onto the suprachiasmatic nucleus regulates numerous behavioral and biological functions as well as circadian rhythms. The accessory optic system targeting terminal lateral, medial and dorsal nuclei through the paraoptic fasciculus plays a role in head and gaze orientation as well as slow movements. Taken together, these neurovisual systems involve 60% of brain activity, thus highlighting the importance of vision in the functioning and regulation of the central nervous system. But vision is first and foremost action, which makes perception impossible without movement. Binocular coordination is a prerequisite for binocular fusion of the object of interest on the two foveas, thus ensuring visual perception. The retino-collicular pathway is sufficient to elicit reflexive eye movements with short latencies. Thanks to its motor neurons, the superior colliculus activates premotor neurons, which themselves activate motor neurons of the oculomotor, trochlear and abducens nuclei. At a higher level, a cascade of neural mechanisms participates in the control of decisional eye movements. The superior colliculus is controlled by the substancia nigra pars reticulata, which is itself gated by subcortical structures such as the dorsal striatum. The superior colliculus is also inhibited by the dorsolateral prefrontal cortex through a direct prefrontotectal tract. Cortical areas are crucial for the triggering of eye movements: the frontal eye field, supplementary eye field, and parietal eye field. Finally the cerebellum maintains accuracy. The focus of the present research topic, entitled Neural bases of binocular vision and coordination and their implications in visual training programs, is to review the most recent findings in brain imaging and neurophysiology of binocular vision and coordination in humans and animals with frontally-placed eyes. The emphasis is put on studies that enable transfer of knowledge toward visual training programs targeting visual field defects (e.g., hemianopia) and binocular functional disorders (e.g., amblyopia).